Causes of altered liver function tests – the role of alpha-1 antitrypsin - Stollenwerk, J.; Schepke, M.; Biecker, E. (Zeitschrift für Gastroenterologie, 2016)
Background: Altered liver function tests are a common finding in clinical practice. Our retrospective study aimed to identify the diagnoses in a non-selected cohort of patients with altered liver tests and to investigate whether alpha-1 antitrypsin genotyping should be part of the diagnostic workup.Patients and Methods: 501 patients who were admitted to our outpatient clinic for further evaluation of altered liver function tests were included in the study. The patients underwent a standardized diagnostic program with history taking, physical examination, laboratory tests and ultrasonography. Liver biopsy was performed if appropriate.Results: More than 50 % of the patients had nonalcoholic fatty liver disease. Alcoholic and drug-induced liver injury were found in 8.6 % and 7 % of patients, respectively. Chronic hepatitis B and C, autoimmune liver disease and inherited causes of liver disease made up for approximately 16 % of the diagnoses. The remaining patients were diagnosed with kryptogenic liver disease or had miscellaneous diagnoses. In 3.7 % of the genotyped patients, the alpha-1 antitrypsin genotype PiMZ was found.Conclusion: Nonalcoholic fatty liver disease is nowadays the most frequent cause of altered liver tests. Alcoholic liver disease might be underrepresented in our study since these patients less often seek medical attention or the diagnosis is already made by the primary care physician. Drug-induced liver injury was found in more patients than expected and might therefore be underdiagnosed in practice. The alpha-1 antitrypsin genotype PiMZ was found in absence of other possible causes of liver disease, indicating that the PiMZ genotype is itself a risk factor for liver disease. Genotyping for alpha-1 antitrypsin should therefore be done when other causes for altered liver function tests have been ruled out.
Keywords: Erhöhte Leberwerte; NAFLD; toxischer Leberschaden; Alpha-1 Antitrypsin